Impact of expensing employee stock options and performance shares under FRS 102 on Singapore listed companies' profit before tax and diluted earnings per share. - Choo, Ying Ying. (2008)
In this paper, we study the implication of expensing Employee Stock Options (ESOs) and Performance Shares (PSs) under the requirement of FRS 102 and FRS 33 on companies' Profit before Tax (PBT) and diluted Earnings per Share (EPS). Throughout our research, Black-Scholes-Merton Model is used to price the fair value of the ESOs and PSs.